Effect of various conditions on adhesively bonded glass fiber reinforced plastic (GFRP) - Lim, Anthony Wee Liang. (Universiti Malaysia Sarawak, UNIMAS, 2008)
Durability of the adhesive joint is one of the most important requirements in adhesive bonding. This is because in real life service, adhesive bonding is subjected to aggressive environments such as humidity, heat, corrosive, impact and chemical environments. Therefore, it is important to know the extend of degradation that these environments can do to the adhesive joint. Adhesive selection is also important because each adhesive have its own properties that make it suitable for different types of environments. The purpose of this project is to investigate four different types of environmental effect on the adhesive joints of GFRP-GFRP (composite) plate using two types of adhesives; one is of toughened epoxy and another one is of chemical resistance epoxy adhesives. The duration for the tests is 3 weeks and 6 weeks for three environments (room temperature, seawater and outside). For the heat test, the duration of the exposure is 1 days and 2 days respectively. The result of the environmental test is found using Shimadzu Autograph machine and graphs for the specimens will be tested and compared.